White Eagle, Black Madonna : One Thousand Years of the Polish Catholic Tradition - Alvis, Robert E. (Book collections on Project MUSE., 2016)
White Eagle, Black Madonna charts the remarkable journey of the Polish Catholic community from its tenth-century origins on the eastern edge of medieval Christendom to the twenty-first century, when a Pole occupied the See of Peter. One constant has been Catholicism's profound influence over Poland's political, social, and cultural life.